NEWS NOTES. - Trumbull, Wendell (The Accounting Review, 1965)
This article presents information on issues related to various accounting bodies in the United States. Some of officers who were elected at the annual meeting of the American Accounting Association (AAA) at Bloomington, Indiana on September 1, 1964 are Robert K. Mautz of the University of Illinois, Herbert E. Miller of Michigan State University and Wilton Anderson of Oklahoma State University. The membership of the AAA at the convention voted, upon recommendation of the executive committee, to change the dues structure of the association effective from January 1, 1965. Dues for full members are now $10.00 per year, for associate members, $3.00 per year and for foreign members, $6.50 per year. The twenty-sixth annual conference of the Institute on Accounting was held at the Ohio State University, Columbus, Ohio, on November 6, 1964. The National Association of Estate Planning Councils held its first annual meeting on September 25, 1964 in New York City. The Association's membership is made up of accountants, attorneys, life underwriters and trust officers.